Growth problems in a sample of children with an Autism Spectrum Disorders and its relation to some variables disorder intensity and age - Al Refae, Alea; Saka, Mare (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The study aimed to identify growth problems in a children with an Autism Spectrum Disorders depending on the variables of disorder intensity and age. The study included 28 children (sample) ,8 cases that are classified as simple , medium, and 20 cases with a high degree. The sample also divided according to the age of 16 children aged (5-6) years and 12 children aged (7-11) years were selected from Syrian Organization for Persons with Disabilities _Aamal To achieve the goal of the study, researcher developed a scale of 36 items divided into 8 fields . The results showed growth problems on all dimensions where (time regulation , locative regulation ,psychomotor perception , behavior , communication , body image ) got a middle score. While the kinetic skills dimension and kinetic coordination were poorly evaluated. The result of the first hypothesis indicated differences in favor of children with high evaluation in all sub-dimensions except kinetic skills dimension and kinetic coordination. The result of the second hypothesis also indicated differences in favor of children aged (7-11) years on psychomotor dimensions (behavior, psychomotor perception , kinetic skills , kinetic coordination , locative regulation ) Study Recommendations: Through the results of the current study, the researcher reached a number of recommendations in this area the need to raise awareness of the importance of Psychomotor growth in children and how to provide a supportive environment.